Decision Ethics and Risk Mitigation: Asset Protection in the Moses–Khidr Narrative - Khaidar rahmaini Jamila; Mustafa Khamal Rokan; Azhari Akmal Tarigan (International Journal of Economics, Science, and Education, 2025)
Purpose: This study aims to examine the ethics of decision-making and risk mitigation in the Qur’an through the narrative of Prophet Moses and Khidr (peace be upon them) in Surah Al-Kahf verse 71, and to explore its relevance to asset protection and contemporary Islamic insurance. Design/methodology/approach: The study employs a qualitative descriptive approach with library research. The main reference is Tafsir Al-Iqtishodiy by Rafiq Yunus Al-Mishri, analyzing the dialogue between Moses and Khidr to extract ethical and economic lessons on risk identification and mitigation. Findings: Khidr’s actions exemplify wisdom-based decision-making and long-term risk mitigation aligned with maqāṣid al-sharī‘ah, particularly hifẓ al-māl. Asset protection is presented as a moral and social responsibility, while takaful, ta‘āwun, and prudence in Islamic insurance reflect Qur’anic ethics of risk management. Research limitations/implications: The study is limited to textual analysis of one Qur’anic narrative and one tafsir perspective, which may constrain generalization. Practical implications: Findings provide an ethical foundation for sustainable risk management and development of Sharia-compliant insurance policies. Originality/value: The study bridges Qur’anic ethics, Islamic decision-making, and modern risk management, offering a novel conceptual framework for ethical asset protection. Paper type: Research paper Keywords: Asset Protection, Decision Ethics, Islamic Insurance, Quranic Interpretation, Risk Mitigation